2015
DOI: 10.1097/ajp.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pain and Developmental Outcomes in Children Born Preterm

Abstract: For infants born preterm, neonatal pain-related stress was associated with alterations in both early and in later developmental outcomes. Few longitudinal studies examined the impact of neonatal pain in the long-term development of children born preterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
169
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(198 citation statements)
references
References 57 publications
0
169
0
18
Order By: Relevance
“…Insufficient use of analgesics has also been observed in other studies in NICUs (5)(6)(7) . The association between neonatal pain experiences in preterm infants and the implications of these children's development are the results of a systematic review that points to a negative impact on postnatal growth and brain development, in addition to negative effects on attention, and cognitive, emotional and motor development (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient use of analgesics has also been observed in other studies in NICUs (5)(6)(7) . The association between neonatal pain experiences in preterm infants and the implications of these children's development are the results of a systematic review that points to a negative impact on postnatal growth and brain development, in addition to negative effects on attention, and cognitive, emotional and motor development (8) .…”
Section: Introductionmentioning
confidence: 99%
“…i n critically ill neonates, pain-related stress affects developmental outcomes, so appropriate pain management is paramount (1). Opioid infusions, sometimes in combination with benzodiazepines, are commonly administered with the intent to decrease pain, agitation, and stress responses in neonates exposed to frequent procedures, during mechanical ventilation, or during therapeutic cooling for hypoxic-ischemic encephalopathy (HIE).…”
mentioning
confidence: 99%
“…Recently, there has been an investment in studies with prospective-longitudinal designs aiming to examine the impact of the exposure to neonatal pain-related stress on the development of the child. A systematic review of the literature showed that acute pain-related stress events experienced in the early neonatal phase have a negative impact on the development of the child, even when controlling for the clinical severity of illness of the preterm newborn samples (Valeri, Holsti, & Linhares, 2015). This review showed that in infants born extremely preterm greater numbers of painful procedures were associated with delayed postnatal growth, poor early neurodevelopment, high cortical activation and altered brain development.…”
Section: Impact Of Pain On Developmentmentioning
confidence: 99%